ENHANCING ISLAMIC SOCIAL REPORTING: THE INTERPLAY OF PROFITABILITY AND SHARIA SUPERVISORY BOARD EFFECTIVENESS - Afroh, Ibna Kamilia Fiel; Hafidzi, Achmad Hasan; Yuliarti, Norita Citra; Rachmawati, Lia; Widyani, Inneke Putri; Wijayantini, Bayu (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to explore the interrelationship between profitability and the effectiveness of Sharia Supervisory Board (SSB) size in enhancing Islamic Social Reporting (ISR). The research focuses on companies listed on the Sharia Stock Index. Employing Path Analysis and the Robust Sobel Test for data analysis, the study reveals that the size of the Sharia Supervisory Board significantly impacts both ISR and profitability. Additionally, profitability plays a crucial role in influencing ISR, with the size of the SSB indirectly affecting ISR through its mediation of profitability. The findings offer valuable insights for managers of Sharia-compliant firms, highlighting key variables that influence corporate social responsibility (CSR) initiatives within these organizations. Consequently, Sharia companies can better determine the critical components for reporting. The study points out the importance for company management to devise strategies that not only focus on enhancing profitability but also ensure that such profitability is leveraged to support CSR activities. This approach fosters a synergistic relationship between financial performance and social responsibility, promoting sustainable business practices aligned with Sharia principles.